Enhanced Charge Transport and Broad Absorption Enabling Record 18.13% Efficiency of PM6:Y6 Based Ternary Organic Photovoltaics with a High Fill Factor Over 80%. (14th December 2021) - Zeng, Yihan; Li, Danqin; Wu, Hongbo; Chen, Zeng; Leng, Shifeng; Hao, Tianyu; Xiong, Shaobing; Xue, Qifan; Ma, Zaifei; Zhu, Haiming; Bao, Qinye
Abstract: Ternary architecture is an efficient strategy to boost desired power conversion efficiency of single‐junction organic solar cells (OSCs). Here, a ternary OSC by incorporating a compatible acceptor ITIC‐M as a third component into state‐of‐the‐art PM6:Y6 blend is reported, yielding a power conversion efficiency of 18.13% and an impressive fill factor of 80.10%. The efficiency is the highest record for the PM6:Y6 based ternary devices reported to date. The full advantages of the designed ternary heterojunction are the good complementary light absorption that increases the photocurrent, and the matched interfacial electronic structures featuring so‐called pinning energies that facilitate exciton separation and suppress charge recombination loss. Furthermore, ITIC‐M plays a vital role in optimizing the micromorphology of the ternary blend with better dispersity, well‐formed fibrillar structure and enhanced crystallinity, thus boosting the charge transport and device performance. Abstract : Highly efficient state‐of‐the‐art PM6:Y6 based organic solar cells with a ternary architecture are achieved, which feature a record efficiency of 18.13% and an impressive fill factor of 80.10%.